Eco-friendly corrosion inhibitors : principles, designing and applications - Guo, Lei; Verma, Chandrabhan; Zhang, Dawei (Elsevier, 2022)
Eco-Friendly Corrosion Inhibitors: Principles, Designing, and Applications wraps up new developments in corrosion inhibitors and their current applications in real-life environments such as in strong acidic pickling and petroleum-based liquids. The book covers several types of environmentally-friendly corrosion inhibitors in detail. In addition, it highlights both established research and technology on industrial scale corrosion inhibitors and their rapidly emerging aspects and future research directions.